Aplikasi Mobile Sederhana Ulfa’s Flower Shop dengan Bahasa Dart Menggunakan Framework Flutter - Ulfa Ladayya; Nuur Wachid Abdulmajid (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
Abstract: Times are growing, technology is not a foreign thing to humans around the world. Technology has entered the life of every layer of society. With the existence of technology, all human activities become easier. One example is the existence of an application that makes it easier for everyone to solve their problems. For example, looking for the desired flower in a flower shop. As is known, flowers are very popular with all walks of life. Often, if there is an event, someone will definitely buy a bouquet of flowers to give to the person they are aiming for. However, the problem that occurs is ignorance of what types of flowers are in the shop. Don't even know if the shop sells the flowers they're looking for. The purpose of making articles from this application is so that consumers can easily see the types of flowers in the shop, details of the flowers, and also order flowers just to be stored so they don't run out and order greeting cards. The method used is the survey method, literature review, and ADDIE development model. This application is built from the Dart language with the Flutter framework. With the existence of technology, we can take advantage of it by building applications to market the business that is being carried out. Of course, an information application like the one the researcher made can make it easier for users to search for the types of flowers available, prices, and the colors that they want to buy without having to go to the store.